Entrepreneurial Framing and Negotiations of Product Boundaries: A Qualitative Study on the Social Construction of Product Innovation in AI Ventures - Zebhauser, Jonathan; Rothe, Hannes; Sundermeier, Janina; Koranteng, Samuel (Proceedings of the International Conference on Information Systems, 2023)
The diffusion of AI-technology disrupts labor and industries and gives rise to a diverse range of new ventures and product innovations. Such product innovations involve the negotiation of product boundaries among actors in innovation networks, including ventures, investors, and customers. These negotiations consist of social and cognitive translations. For digital products, actors share a common understanding of resource configuration, mainly based on cognitive resonance. However, AI-driven products introduce the “black-box” problem that hinders cognitive translation-based negotiations within innovation networks, as they are not fully cognitively traceable, but emotionally resonant. Using a qualitative research approach and the notion of entrepreneurial framing, we investigate the impact of AI on the negotiation of product boundaries and digital innovation. We reveal that AI-ventures, to maintain ”cognitive” superiority, focus on cutting-edge technology while limiting negotiation to non-technology aspects, such as revenue streams and business models, creating ”cognitive moats” for non-expert actors.